Chromozomální integrace sestého lidského herpesviru (HHV-6) - Hubácek, Petr; Hrdlicková, Alena; Zajac, Miroslav (Epidemiologie, mikrobiologie, imunologie, 2012)
Two closely related and commonly found human herpesviruses HHV-6 A and HHV-6 B are classified into the sixth human herpes virus complex (HHV-6). Primary infection with HHV-6 often takes place in early childhood and it can be either asymptomatic or manifests itself as sixth disease (caused by HHV-6 B). HHV-6 remains present in a latent form in the body with the potential for virus reactivation. The article points out the phenomenon of chromosomal integration of HHV-6 (Ci-HHV-6) which is found in about 1% of the population and, unlike the commonly spread HHV-6 infection, has become hereditary, with its pathological potential in Ci-HHV-6 DNA carriers remaining unknown. Therefore, the focus on clinical consequences of Ci-HHV-6 is of high relevance to the therapeutic strategy for patients with high HHV-6 positivity in molecular biological tests.
Keywords: přenašečství; Herpesvirus 6, Human; lidský herpesvirus 6; lidé; Virus Integration; exanthema subitum; Exanthema Subitum; Humans; Carrier State; integrace viru